Pulmonary tuberculosis of occupational origin in a funeral director: A case report - Anna Witkowska; Marta Wiszniewska; Anna Krakowiak; Jolanta Walusiak-Skorupa (Nofer Institute of Occupational Medicine, 2014)
In Poland the incidence rate of tuberculosis is higher than the average for countries of the European Union, Norway or Iceland. On the other hand, occupational tuberculosis is still rarely recognized in our country. In this paper we present the first in Poland- to our best knowledge - case of pulmonary manifestation of this disease acquired at work in a funeral director. The recognition of the occupational etiology of the discussed illness gave rise to an array of diagnostic problems and became feasible after a thorough analysis of the patient's history and literature data, which allowed finding the relationship between infection and performed job. We speculated that the transfer of the dead body and handling of cadavers may expel residual air from the lungs of the deceased. Although tuberculosis occurs frequently in the general population, the recognition of work-related cases of this disease is still rare, especially among funeral directors. Med Pr 2014;65(3):429-435